Study on Metakaolin Impact on Concrete Performance of Resisting Complex Ions Corrosion - Xupeng, Chen; Zhuowen, Sun; Jianyong, Pang (Frontiers in Materials, 2021)
The main purpose of this study is to determine the metakaolin (MK) impacts on the concrete durability when the concrete is subjected to joint corrosion of SO42−,Mg2+ and, Cl−. Four groups of concrete test samples, which contained different MK contents, were designed and tested in order to see their physical property changes and macro-morphology differences during the cyclic corrosion process. And a series of approaches, including XRD, FTIR, SEM, and EDS, were applied to study the concrete phase composition changes and the micro-morphology features of all groups. According to the test results, when reaching 20 cycles, the concrete sample with 10% MK showed the best concrete physical properties; when reaching 120 cycles, the concrete with 5% MK content showed the best durability, produced similar amount of corrosion products to ordinary concrete, and presented relatively compacted micro-structure and small internal porosity. Mg2+ actually has a great impact on metakaolin. The corrosion product quantity increased significantly when MK admixture reached 15%. Due to the great number of produced M-S-H, the corrosive ions damaged the concrete for a second time, leading to serious aggregate peeling-off, powder surface of test samples, and porous micro-structure.